2022
DOI: 10.1186/s13017-022-00418-y
|View full text |Cite
|
Sign up to set email alerts
|

WSES guidelines on blunt and penetrating bowel injury: diagnosis, investigations, and treatment

Abstract: The aim of this paper was to review the recent literature to create recommendations for the day-to-day diagnosis and surgical management of small bowel and colon injuries. Where knowledge gaps were identified, expert consensus was pursued during the 8th International Congress of the World Society of Emergency Surgery Annual (September 2021, Edinburgh). This process also aimed to guide future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 119 publications
0
38
1
4
Order By: Relevance
“…The possible reason might be that low hemoglobin concentration reduces the oxygen tension in the wound site and increases the risk of SSI by compromising the activity of blood cells such as macrophages and delaying the process of infection healing (32,33) Those patients admitted to the intensive care unit had 21.3 times higher odds of death as compared to those who were not admitted to the intensive care unit. In the guidelines of the World Society of Emergency Surgery (WSES), admission to the ICU is recommended for the management of penetrating abdominal trauma (34). However, in the present study, ICU admission was found as a risk factor.…”
Section: Characteristicscontrasting
confidence: 70%
“…The possible reason might be that low hemoglobin concentration reduces the oxygen tension in the wound site and increases the risk of SSI by compromising the activity of blood cells such as macrophages and delaying the process of infection healing (32,33) Those patients admitted to the intensive care unit had 21.3 times higher odds of death as compared to those who were not admitted to the intensive care unit. In the guidelines of the World Society of Emergency Surgery (WSES), admission to the ICU is recommended for the management of penetrating abdominal trauma (34). However, in the present study, ICU admission was found as a risk factor.…”
Section: Characteristicscontrasting
confidence: 70%
“…Other reports have, however, indicated a wide range in negative laparotomy incidences ranging from 6 to 36% [7,41,42,45,[49][50][51][52][53][54][55]. A further analysis of the negative laparotomy patients revealed that 77% of these were operated solely due to evidence of peritoneal penetration with signs of associated injury, a protocol that remains debatable and not supported by neither the Eastern Association of Trauma (EAST), Western Trauma Association (WTA) or the World Society of Emergency Surgery guidelines [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive CT-Befunde wie freie Flüssigkeit ohne Verletzung eines parenchymatösen Organs, pathologische Kontrastmittelaufnahme der Darmwand oder eine mesenteriale Imbibierung können zur Entscheidungsfindung beitragen, sollten jedoch nicht alleinige Kriterien sein. Um die insgesamt eingeschränkte Sensitivität des CTs zu erhöhen, wurden Scoring-Systeme etabliert, die durch Kombination der vorgenannten Befunde die Sensitivität und Spezifität erhöhen können 15 .…”
Section: Therapieunclassified
“…Insbesondere bei Dünndarmverletzungen ist aufgrund der guten Heilungstendenz mit Insuffizienzraten von 3% die Anastomose der Diskontinuitätsresektion vorzuziehen. Bei Kolonverletzungen steigt jedoch die Insuffizienzrate, je weiter distal die Anastomose angelegt wird, auf bis zu 50% 15 . Auch die verzögerte Anlage der Anastomose im Rahmen der Zweitoperation sowie das offene Abdomen ist mit erhöhten Insuffizienzraten assoziiert.…”
Section: Therapieunclassified
See 1 more Smart Citation